Applications of maqasid al-shariah in Islamic finance an analysis - Md Habibur, Rahman (2019)
Considering the indispensability of wealth in human life, Islam instead of negating puts special emphasis on wealth. Even preservation of wealth is regarded as one of the ma q āsid al Sharīʻah (objectives of Sharīʻah) in Islam. To guide human being in this regard, Islam has prescribed as well as proscribed necessary injunctions. This paper aims to shed light on three crucial sectors pertaining to Islamic Finance namely Islamic Banking, Islamic Capital Market and Takaful (Insurance) in the light of maq āsid al Sharīʻah. The author painstakingly endeavors to prove that Islamic jurists, in delineating maq āsid al Sharīʻah regarding property, has intensely explicated the issues of acquisition, investment, mobilization and expenditure of property with special emphasis on justice, transparency, proscription against illegal grabbing etc. He advances the argument that proper compliance with the principles of Islamic Finance inevitably ensures the realization of both specific and general maq āsid al Sharīʻah. Moreover, the paper splendidly spells out that edicts of Islamic Finance encompass the dynamism to warrant mobility in investment and mobilization of Sharīʻah permitted property, ensure justice and fair distribution of property, sweep away illegal grabbing, preserve property and improve the faith and character of concerned persons.